Difference of metalinguistic representation of declarative clause (subordinata dichiarativa) in Italian academic and educational literature - Melnikova, Liudmila S. (Journal of the Belarusian State University. Philology, 2019)
The article identifies differences in theoretical description of declarative clause in academic and educational literature, defines an equivocation of its status in the system of subordinating constructions in Italian language and introduces an abstract model of this object. For the first time a detailed analysis of theoretical description of declarative clause in Italian language is held and an in-depth list of its characteristics is compiled. The results give an opportunity to optimize the study of parsing a compound sentence.